Efficacy of Ultrasound on Pre-fermentation Maceration in Red Dragon Fruit Winemaking - Nguyen Phuoc Minh (Journal of Global Pharma Technology, 2016)
Ultrasound has recently been applied to evaluate the possible effect on color and flavor extraction at different stages of the winemaking process. Red color and aromatic compounds are localized in the skin cells and their release is facilitated by mechanical actions, disruption of tissues and cells, temperature and alcohol. Red dragon fruit has various nutrients, vitamins and minerals and medicinal values. Our present research focused on the effect of power and time of ultrasound as pretreatment maceration in red dragon fruit winemaing. Results revealed that using ultrasound power 270 w in 20 minutes as a pre-treatment on crushed red dragon fruit for the extraction of polyphenol, aromas. The application of ultrasounds allowed a significant reduction of the maceration duration and to get high-quality wine with high alcohol content, total phenolic, and good sensory characteristics.Keywords: Red dragon fruit, Ultrasound, Maceration, Power, Duration, Winemaking.